2023
DOI: 10.7150/ijms.80207
|View full text |Cite
|
Sign up to set email alerts
|

Significant impact of body mass index on the relationship between increased white blood cell count and new-onset diabetes

Abstract: An elevated white blood cell (WBC) count has been linked to incident diabetes. WBC count has been positively associated with body mass index (BMI), and elevated BMI has been reported to be a strong predictor of future diabetes. Hence, the association of increased WBC count with the subsequent development of diabetes may be mediated by increased BMI. This study was designed to address this issue. We selected subjects from the 104,451 participants enrolled from 2012 to 2018 in the Taiwan Biobank. We only include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
0
0
1
Order By: Relevance
“…Additionally, Chatterjee and colleagues reported that a high leukocyte count leads to dysregulated blood glucose levels, reducing the likelihood of restoring normal glucose levels [ 53 ]. Recent studies have indicated that an increased leukocyte count is associated with the onset of T2DM, and a BMI greater than 25 kg/m 2 may mediate this association [ 54 ]. Gu et al reported that the leukocyte count could serve as an indicator of whether obesity increases the risk of developing diabetes [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Chatterjee and colleagues reported that a high leukocyte count leads to dysregulated blood glucose levels, reducing the likelihood of restoring normal glucose levels [ 53 ]. Recent studies have indicated that an increased leukocyte count is associated with the onset of T2DM, and a BMI greater than 25 kg/m 2 may mediate this association [ 54 ]. Gu et al reported that the leukocyte count could serve as an indicator of whether obesity increases the risk of developing diabetes [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeks massa tubuh memiliki pengaruh signifikan dengan perubahan jumlah relatif sel darah putih. perubahan tersebut didominasi dengan peningkatan sel darah putih (12,13). Kebiasaan merokok meningkatkan potensi terkena peradangan yang akan mempengaruhi sistem imun.…”
Section: Hasil Dan Pembahasanunclassified